2016
DOI: 10.1007/s12552-016-9161-1
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Mobility of Families Raising Children in the Twenty-First Century

Abstract: Wealth inequality between the top and bottom deciles has grown over the last 20 years (Piketty and Zucman in Wealth and inheritance in the long run, Centre for Economic Policy Research, London, 2014), as has the racial wealth gap (Shapiro et al. in The roots of the widening racial wealth gap: explaining the black-white economic divide. Institute on Assets and Social Policy, Brandeis University, Waltham, 2013. http://iasp.brandeis.edu/pdfs/Author/sha piro-thomas-m/racialwealthgapbrief.pdf). Within these broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Identification of these key variables, their patterns and how they are differentially impacted dependent on one's individual race, "highlights the need for targeted policies that reinforce and expand opportunities for all families to build wealth over the life course" (Meschede et al, 2016, p. 77). The study conducted by Meschede et al (2016) highlighted "larger family transfers [(family capital)], consistent long-term homeownership [and] resources available within a community [(neighbourhood capital)], …white-collar occupations [(employment capital)]" (p. 77), human capital, and social capital as the primary factors which influence wealth mobility. This will serve as the groundwork of this study; and these main themes will be discussed in this chapter.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 99%
“…Identification of these key variables, their patterns and how they are differentially impacted dependent on one's individual race, "highlights the need for targeted policies that reinforce and expand opportunities for all families to build wealth over the life course" (Meschede et al, 2016, p. 77). The study conducted by Meschede et al (2016) highlighted "larger family transfers [(family capital)], consistent long-term homeownership [and] resources available within a community [(neighbourhood capital)], …white-collar occupations [(employment capital)]" (p. 77), human capital, and social capital as the primary factors which influence wealth mobility. This will serve as the groundwork of this study; and these main themes will be discussed in this chapter.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 99%
“…With home ownership as the key vehicle of wealth accumulation, these inequalities also translate into large racial gaps in net worth. Racial wealth gaps have grown over time and across the life-course and can be found even among otherwise more privileged segments of the population, such as the college educated (Meschede et al 2016;Taylor and Meschede 2018).…”
Section: Racial and Ethnic Inequalitymentioning
confidence: 99%
“…Killewald (2013) examined panel data from 1980 to 2009 and observed that among wealth holders, Black families were significantly disadvantaged compared to similar White families; much of the difference is due to parental wealth. Meschede et al (2016) observed that people living in neighborhoods with high concentrations of poverty and families with a Black head-ofhousehold had lower levels of absolute wealth mobility, or the ability to grow wealth. Hamilton et al (2015) explored recent trends in wealth disparities by race and demonstrated consistently lower levels of wealth accumulation rates for people of color compared to Whites, even after controlling for education level, income, and employment.…”
Section: Wealthmentioning
confidence: 99%